Strategy for Improving the Quality of Education at the YAPIS Oesmaniyah Madrasah Aliyah, North Jakarta - Qudsi, Qudsi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This study aims to examine the strategy for improving the quality of education at the Yapis Al-Oesmaniyah Islamic Senior High School focusing on content standards, process standards, and educator standards. This study uses a qualitative phenomenological approach with data collection through interviews, observation, and document collection. Data analysis begins with the review, reduction, explanation, and conclusion while checking the validity of the source type data, which is carried out to confirm new data or information obtained from other sources. The results of the study in this study found a strategy for improving the quality of education at the Yapis Al-Oesmaniyah Islamic Senior High School through the development of 3 National Education Standards including content standards, namely by combining the Islamic boarding school curriculum with the school curriculum, then the process standard uses an approach based on field practice and the educator standard has 5 teacher competitions including competence, personality, pedagogical, social, professional and one ideology. Keywords: Strategy, Quality Improvement, Madrasah Education